Kedudukan Akta Jual Beli Tanah Milik Anak di Bawah Umur Tanpa Adanya Izin Pengadilan (Studi Putusan Pengadilan Negeri Surakarta Nomor 100/Pdt.G/2021/PN.Skt) - Sekar Puspita Arum (UNES Law Review, 2023)
Parents and guardians are authorized to represent the legal actions of minors. According to the Civil Code, the authority of parents to act on behalf of their children has limitations, namely to transfer immovable property belonging to minors must be determined by a permit to sell from the district court. In this case, the parents sold the minor's land without permission to sell from the district court, but with a Certificate of Guardianship from the village. The purpose of this study is to analyze the provisions regarding the appointment as guardian for parents who live the longest to be able to act on behalf of their children and the position of the deed of sale and purchase of land owned by minors made without court permission. The method used in this research is doctrinal research. The result of this research is that the appointment as guardian is not required for parents who live the longest to be able to act on behalf of their children. This is because according to the Marriage Law, Compilation of Islamic Law, and Supreme Court Circular Letter No. 7/2012, the longest living parent continues to exercise parental authority and does not change into guardianship even though the marriage ends due to the death of one of the parents. The position of the deed of sale and purchase of land owned by a minor in this case remains valid even without permission to sell from the district court because the seller is not subject to the Civil Code.